(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
The free training project MOVE HEALTHY, which started in Kaunas in 2013, was initiated by members of the public, and was later taken over by the Kaunas City Municipality, together with the city’s Public Health Bureau. The idea behind the project was to give the citizens of Kaunas the opportunity to be maximally active, receiving free services in attractive and convenient locations in the city. Currently, Kaunas residents can participate in up to thirty training sessions per week organised by the project, which are suitable for everyone, regardless of their physical capacity. Every age group can choose classes of suitable intensity: from calm yoga or Pilates training, to intense functional, Zumba dance, or running training. Free training and exercises are held all year round, all week, on weekdays. Training is conducted in different public spaces and micro-districts of Kaunas and annually attracts thousands of Kaunas people who love a healthy and active lifestyle. During the summer season, classes take place in the fresh air, in parks. The MOVE HEALTHY project, financed by the Kaunas City Municipality, also delights the citizens of Kaunas with various additional activities, such as orientation games, big sports events, or training on the roof of a building with a picturesque panorama of the city of Kaunas or training in the football stadium. During the free training project MOVE HEALTHY, special attention is paid to the trainers, thus the classes are conducted only by professional trainers with many years of experience, who not only help to perform the exercises correctly, but also guarantee the participants a great mood and motivate them to move in mass training sessions full of positivity and energy. Specialists of the Kaunas City Municipality Public Health Bureau, project coordinators, are trying to involve as many Kaunas residents as possible in the activities, therefore the project is constantly developing: the variety of training is increasing, more different age groups are included. Project MOVE HEALTHY promotes a healthy lifestyle by ensuring free and inclusive access to physical activity. It provides long-term benefits to public health in Kaunas.